PENGEMBANGAN MODUL PRAKTIKUM EFEK FOTOLISTRIK BERBASIS VIRTUAL LABORATORY DENGAN MODEL DISCOVERY LEARNING - Helena Mogi; Theresje Mandang; Jimmy Lolowang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
This research is motivated by the absence of a virtual laboratory-based practicum module to be used as a mandatory guide for students. So that students find it difficult to understand the concepts of physics related to the photoelectric effect practicum, especially in this pandemic era. This research aims to develop a Virtual Laboratory-Based Photoelectric Effect Practicum Module Using a Discovery Learning Model. This study is a research and development study using the 4D research model adapted from the Thiagarajan model, namely define, design, develop, and disseminate. The results of the study for students got an average value of 82.75%, so that the module was included in the feasible / valid category. And in response 57.35% of students chose very useful (SB), 42.65% of students chose useful (B), and no student chose less useful (KB) and not useful (TB). Based on the research results, it can be concluded that the product has been produced in the form of a photoelectric effect practicum module based on a virtual laboratory using a discovery learning model with good and proper qualifications.